The internal and external responses to a forward-specific rugby league simulation protocol performed with and without physical contact - Mullen, T.; Highton, J.; Twist, C. (International Journal of Sports Physiology and Performance, 2015)
It is important to understand the extent to which physical contact changes the internal and external load during rugby simulations that aim to replicate the demands of match play. Accordingly, this study examined the role of physical contact on the physiological and perceptual demands during and immediately after a simulated rugby league match. Nineteen male rugby players completed a contact (CON) and a noncontact (NCON) version of the rugby league match-simulation protocol in a randomized crossover design with 1 wk between trials. Relative distance covered (ES = 1.27; ±0.29), low-intensity activity (ES = 1.13; ±0.31), high-intensity running (ES = 0.49; ±0.34), heart rate (ES = 0.52; ±0.35), blood lactate concentration (ES = 0.78; ±0.34), rating of perceived exertion (RPE) (ES = 0.72; ±0.38), and session RPE (ES = 1.45; ±0.51) were all higher in the CON than in the NCON trial. However, peak speeds were lower in the CON trial (ES = -0.99; ±0.40) despite unclear reductions in knee-extensor (ES = 0.19; ±0.40) and -flexor (ES = 0.07; ±0.43) torque. Muscle soreness was also greater after CON than in the NCON trial (ES = 0.97; ±0.55). The addition of physical contact to the movement demands of a simulated rugby league match increases many of the external and internal demands but also results in players` slowing their peak running speed during sprints. These findings highlight the importance of including contacts in simulation protocols and training practices designed to replicate the demands of real match play.